Diagnosis, Evaluation, and Management of renal diseases during Pregnancy - Jorge Francisco Perez-Oliva Diaz; Roberto Cantero Hernández; Jorge Díaz Mayo; Regino Antonio Oviedo Rodríguez; Runiel Tamayo Pérez (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The high prevalence of chronic kidney disease and others non contagiables diseases, jointly with its increasing frequency in gestational age women have generated new investigations and evidences of the relationship between the chronic renal diseases, the pregnancy and its consequence for the mother and fetus. Objective: This paper summarizes the best practice up to this date and provides a reasonable approach to the diagnosis, evaluation, and treatment of the Renal Disease Disorders of Pregnancy to evaluate the impact of them on maternal and fetal morbidity and mortality. Material and Methods: An analysis of the published literature of the subject was performed, describing the best clinical results based on scientific advances available today. Results: Was emphasized the continuum evolution between acute kidney damage (incipient injury) and acute kidney failure (need to dialysis) also of importance for prognosis, with increasing of the mortality associated with small increases in serum creatinine. Conclusions: The acute kidney diseases/ acute renal failure and chronic renal diseases are important causes of maternal and perinatal morbidity - mortality. Keywords: Healthy pregnancy, Chronic non contagiables diseases, Acute renal damage, Acute renal failure, Chronic kidney disease, Maternal and Perinatal morbidity - mortality.